The foodscape revolution : finding a better way to make space for food and beauty in your garden - Arthur, Brie (St. Lynns Press, 2017)
"Once upon a time, veggie gardens lived in the backyard, isolated from the rest of the landscape. that's so yesterday! Welcome to a whole new world of food gardening--right up front, sharing space with your ornamental plants for year-round, knockout beauty and function ... in a way that even homeowners associations (HOAs) would approve."--Back cover.